2017
DOI: 10.1097/ccm.0000000000002654
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Effects of Prior Acetyl-Salicylic Acid on Sepsis-Related Deaths: An Individual Patient Data Meta-Analysis Using Propensity Matching*

Abstract: Objective The primary objective was to conduct a meta-analysis on published observational cohort data describing the association between acetyl-salicylic acid (aspirin) use prior to the onset of sepsis and mortality in hospitalized patients. Study Selection Studies which reported mortality in patients on aspirin with sepsis with a comparison group of patients with sepsis not on prior aspirin therapy were included. Data sources Fifteen studies described hospital-based cohorts (n=17,065), while one was a lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…A number of clinical studies in patients affected by diseases of different degrees of clinical severity (e.g., critically ill, admitted to ICUs, with sepsis, severe sepsis, community-acquired pneumonia) showed that the use of ASA was associated with lower mortality [ 116 , 117 ]. These beneficial effects of ASA have been confirmed by an individual patient data meta-analysis of published observational cohort data showing a reduced sepsis-related mortality in patients taking ASA prior to the onset of sepsis [ 118 ]. A more recent meta-analysis of ten cohort studies enrolling 689,897 patients with sepsis revealed that ASA, administered either before or after sepsis, reduced ICU or hospital mortality [ 119 ].…”
Section: Clinical Applications Of Acetylsalicylic Acid In Infectious mentioning
confidence: 84%
“…A number of clinical studies in patients affected by diseases of different degrees of clinical severity (e.g., critically ill, admitted to ICUs, with sepsis, severe sepsis, community-acquired pneumonia) showed that the use of ASA was associated with lower mortality [ 116 , 117 ]. These beneficial effects of ASA have been confirmed by an individual patient data meta-analysis of published observational cohort data showing a reduced sepsis-related mortality in patients taking ASA prior to the onset of sepsis [ 118 ]. A more recent meta-analysis of ten cohort studies enrolling 689,897 patients with sepsis revealed that ASA, administered either before or after sepsis, reduced ICU or hospital mortality [ 119 ].…”
Section: Clinical Applications Of Acetylsalicylic Acid In Infectious mentioning
confidence: 84%
“…However, the study only included antiplatelet use in the 30 days prior to admission, and did not differentiate aspirin from other antiplatelet agents. Similarly, in a meta-analysis, Trauer, et al observed 7% lower sepsis mortality among pre-existing aspirin users, but most of the included studies did not differentiate between the use of aspirin and other antiplatelet agents [ 34 ]. Of note, in our series we observed a sepsis hospital mortality rate of only 9.2%, while the studies in the Trauer, et al study reported sepsis mortality ranging from 14 to 42%.…”
Section: Discussionmentioning
confidence: 99%
“…Chen and coworkers found that critically ill patients taking aspirin had a significantly lower prevalence of adult respiratory distress syndrome (ARDS) (27% versus 34%; P ϭ 0.034) (21). Chronic aspirin therapy has been also associated with improved survival rates for both patients with CAP (13) and those with sepsis (22).…”
Section: Discussionmentioning
confidence: 99%